Stimulatory effects of Lycium shawii on human melanocyte proliferation, migration, and melanogenesis: In vitro and in silico studies - Alghamdi, Khalid; Alehaideb, Zeyad; Kumar, Ashok; Al-Eidi, Hamad; Alghamdi, Sahar S.; Suliman, Rasha; Ali, Rizwan; Almourfi, Feras; Alghamdi, Saleh M.; Boudjelal, Mohamed; Matou-Nasri, Sabine (Frontiers in Pharmacology, 2023)
There is no first-line treatment for vitiligo, a skin disease characterized by the lack of melanin produced by the melanocytes, resulting in an urgent demand for new therapeutic drugs capable of stimulating melanocyte functions, including melanogenesis. In this study, traditional medicinal plant extracts were tested for cultured human melanocyte proliferation, migration, and melanogenesis using MTT, scratch wound-healing assays, transmission electron microscopy, immunofluorescence staining and Western blot technology. Of the methanolic extracts, Lycium shawii L. (L. shawii) extract increased melanocyte proliferation at low concentrations and modulated melanocyte migration. At the lowest tested concentration (i.e., 7.8 µg/mL), L. shawii methanolic extract promoted melanosome formation, maturation, and enhanced melanin production, which was associated with the upregulation of MITF, tyrosinase, tyrosinase-related protein (TRP)-1 and TRP-2 melanogenesis-related proteins. After the chemical analysis and L. shawii extract-derived metabolite identification, the in silico studies revealed the molecular interactions between Metabolite 5, identified as Apigenin (4,5,6-trihydroxylavone), and the copper active site of tyrosinase, predicting an enhanced tyrosinase activity and subsequent melanin formation. In conclusion, L. shawii methanolic extract stimulates melanocyte functions including melanin production, and its derived Metabolite 5 is predicted to enhance tyrosinase activity, suggesting further investigation of the L. shawii extract-derived Metabolite 5 as a potential natural drug for vitiligo treatment.